Władysław Witwicki jako filozof - Woleński, Jan (Filozofia Nauki, 1999)
Władysław Witwicki was first of all a psychologist, but he graduated in philosophy from Lvov University, being one of the earliest pupils of Kazimierz Twardowski. He was a representative of the descriptivistic branch of the Lvov-Warsaw School. In the area of phsychology he put into practice the important postulate of his teacher, who persuaded his students to write original handbooks, giving Polish scholar contributions their due: it is how the work on Witwicki's Psychology began. In the area of philosophy he was particularly interested in the foundations of (descriptive) psychology. Witwicki's ontological and epistemological views are close to realism. In ethics he defended the absolute character of moral norms against scepticism and relativism. In general, Witwicki subscribed to anti-irrationalism, the common standpoint in his School.